A cup of friendship [large type] : a novel - Rodriguez, Deborah (Thorndike Press large print core, 2011)
Sunny is an expat in Kabul who blissfully runs a coffee shop for other Americans in the country. When Yazmina, a pregnant young woman from a nearby village, is kidnapped and later abandoned near the coffee shop, Sunny instinctively comes to her aid. Candace, a wealthy American, also pitches in, while Isabel, a journalist, chronicles Yazmina's woe. Meanwhile, Halajan, a local mother, is reeling from a forbidden love affair.